Analisis Imposeks pada Keong Macan (Babylonia spirata spirata) Sebagai Bioindikator Cemaran Tributyltin di Pelabuhan Tanjung Mas Semarang - Kusumastuti, Retno; Widianingsih, Widianingsih; Tri Nuraini, Ria Azizah (977-2407769)
A biondicator approach in knowing the possible contamination of Tributyltin in the water of the Port of Tanjung Mas Semarang study has been carried out analysis imposex the tiger snail (B. spirata spirata). During April-Mei 2013, a total of 127 of the tiger snail were collected from study areas. Analysis on male sexual organs characteristics in female of the tiger snail indicated the extensive imposex phenomenom in study areas with frequency of imposex in population of the tiger snail in the Port of Tanjung Mas Semarang up to 50,84% where size of pseudopenis in female imposex of the tiger snail (Â± 3-10 mm) with a value of Relative Penis Size Index 93,172% with sex ratio between male of the tiger snail and female is 1:3.